WHEN THE EARTH IS NOT ENOUGH: THE ROLE OF OUTER SPACE IN CHINA’S GRAND STRATEGY - Duarte, Paulo Afonso Brardo; Topcu, Neslihan; Santos, Daniel (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
This article assesses China’s Space achievements drawing on realism. Outer Space provides a logic of continuity of a similar assertive stance that already characterises China’s revisionist posture in the South China Sea. We argue that such a realist stance fits well into China’s gradual move towards a flexible perception of borders, despite being a Westphalian State. We aim at answering the following research question: What role does Space exploration play in China’s Grand Strategy and what does it represent for China’s competitive outcomes in terms of economic prowess, military power and even as a source of political prestige and narrative?